The Effect of Learning Agility and Employee Engagement on Employee Performance with Adaptability as a Mediator - Irfan Nurhadi; Osly Usman (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This study was designed to investigate the impact of learning agility and employee engagement on employee performance, with adaptability serving as a mediator. The research employed a quantitative, explanatory design involving 99 employees from the telecommunications and technology-based communication services sectors in Indonesia. Data were collected via a questionnaire using a 1–5 Likert scale and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4. The findings indicate that learning agility has a positive and significant impact on adaptability, while adaptability also has a positive and significant effect on employee performance. Learning agility and employee engagement do not show a significant direct impact on employee performance. Employee engagement also does not have a significant impact on adaptability. Mediation tests show that adaptability fully mediates the effect of learning agility on employee performance, but does not mediate the effect of employee engagement on employee performance. These results emphasize that employees’ learning abilities will be more effective in improving performance when optimized by the ability to adapt to changes in work, technology, and the organizational environment.